Developmental adjustments of house sparrow (Passer domesticus) nestlings to diet composition - Brzek, Pawel (2009)
House sparrow nestlings are fed primarily on insects during the first 3 days of their life, and seeds become gradually more important afterwards. We tested whether developmental changes in size and functional capacity of the digestive tract in young house sparrows are genetically hard-wired and independent of diet, or can be modified by food type. Under laboratory conditions, we hand-fed young house sparrows with either a starch-free insect-like diet, based mainly on protein and fat, or a starch- containing diet with a mix of substrates similar to that offered to older nestlings in natural nests when they are gradually weaned from an insect to a seed diet. Patterns of overall development in body size and thermoregulatory ability, and in alimentary organ size increase, were relatively similar in house sparrow nestlings developing on both diets. However, total intestinal maltase activity, important in carbohydrate breakdown, was at least twice as high in house sparrow nestlings fed the starch-containing diet (P<0.001). The change in maltase activity of nestlings was specific, as no change occurred in aminopeptidase-N activity in the same tissues. There was no significant diet effect on digesta retention time, but assimilation efficiency for radiolabeled starch tended to be higher (P=0.054) in nestlings raised on starch-containing diet. Future studies must test whether the diet-dependent increase in maltase activity during development is irreversible or reversible, reflecting, respectively, a developmental plasticity or a phenotypic flexibility.